On the Early Detection of Intravascular Coagulation - Fedder, G; Prakke, Elisabeth M.; Vreeken, J (Thrombosis and Haemostasis, 1972)
Since the conception of intravascular coagulation has been introduced in clinical medicine, the interest of clinicians in the early detection of this syndrome is continuously increasing. Therefore small amounts of thrombin and thromboplastin were infused into rabbits and special parameters, such as presence of an activated form of factor V and occurrence of a positive fibrin monomer test, were checked. As it turned out, activation of factor V (proaccelerin, accelerator globulin or AcG) was an earlier sign of intravascular coagulation than the appearance of a positive gelation test, which may occur without changes in fibrinogen or the number of blood platelets. These experiments could be of value for the early detection of intravascular coagulation in man.